PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN CORE DALAM UPAYA PENINGKATAN KEMAMPUAN KONEKSI MATEMATIK SISWA - Yazid Yazid; M. Irfan Habibi; Inri Rahmawati (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
This study aims to determine: (1) Whether the mathematical connection ability of students who get models learning CORE is better than students who get learning method lecture (2) Whether improvement mathematical connection ability of students who get models learning CORE is better than students who get learning method lecture 3) How is the response students towards mathematics with models CORE. This experimental study conducted at SMP 1 Lebakwangi in the second half for the academic year 2015/2016 with the draft pretest-posttest control group design. The population in this study were all students of class VII SMP 1 Lebakwangi. Sampling was done by using sampling techniques random simple. From the selected sample, one class into a class experiment, ie classes given models learning CORE and one class as the control class, the classes given learning method lecture. Measurement of mathematical connection ability tests performed using an instrument shaped mathematical connection abilities test description. This instrument has qualified the validity and reliability of the instrument. The results showed (1) mathematical connection ability of students who get models learning CORE is better than students who get learning method lecture. It is based on test results mean difference using the t test which showed (2) Improvement mathematical connection ability of students who get learning models CORE is better than students who get learning method lecture. It is based on test results mean difference using the U test which showed z count > z table yaitu z count = 4,66 > z table = 1,96 (3) The application of mathematics models learning CORE received a positive response based on the student questionnaire.